Research Trends in Problem Based Learning in Middle School (1998-2023): A Bibliometric Review - Christina Monika Samosir; Ilham Muhammad; Febrinna Marchy; Elmawati Elmawati (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Problem-based learning is a learning model that uses real-life problems that require authentic investigations to construct knowledge actively and collaboratively. The aim of this study was to capture the research landscape related to problem-based learning applied to students at the middle school level from 1998 to 2023. A descriptive bibliometric analysis method was used in this study. The data obtained was taken from the Scopus database. The results of the study show that publications related to problem-based learning, especially in middle schools, go up and down every year. Publications in 2003 have been cited more than any other year. The United States of America is the most influential country in this field. publications in journals related to problem-based learning research applied to middle school students are mostly at the Q1 rank, namely 45 journals. The research focus is divided into 3 namely, 1) knowledge, skills and development; 2) effect, self-efficacy, achievement and effectiveness; 3) middle school students, environment and abilities. These three research focuses can be used as a reference for future researchers to determine the focus of their research related to problem-based learning